Cyanogel and its derived-materials: properties, preparation methods, and electrochemical applications. (June 2021) - Lin, Shi-Yi; Yao, You-Qiang; Zhang, Lu; Feng, Jiu-Ju; Wang, Ai-Jun
Abstract: Cyanogel, a novel inorganic polymeric hydrogel, is constituted by chlorometallates and transition-metal cyanometallates, which is thought as fascinating and promising precursor to produce highly alloyed materials with stereochemical structures. In this review, the properties, synthesis methods, and electrochemical applications of the cyanogel and its derivates are systematically discussed. With intrinsic properties such as 3D interconnected backbones, uniform distributions of metals at atomic level, and porous structures, the cyanogel-derived materials exhibit superior activities and stabilities. During the synthesis process, the skeleton of cyanogel serves as soft template for generating metal structures without any surfactant. Due to the versatility and tunability of cyanogels, their derivatives not only provide foreseeable opportunities for preparation of highly efficient nanomaterials in electrocatalytic reactions, but also broaden their practical applications in energy-related devices such as fuel cells, water splitting electrolyzers, metal-air batteries, energy storage batteries, and supercapacitors. Through this review, we aim to provide valuable guidelines for constructing highly effective materials in practice. Graphical abstract: Focus on diverse kinds of cyanogels, we overviewed their properties, synthesis methods, and derived-applications in electrochemistry. By discussing and summarizing the existing applications of different cyanogel precursors clearly, some perspectives are highlighted for synthesis strategies. Image 1 Highlights: Cyanogel has unique 3D structure, high hydrophilicity, and uniform distribution of metals. The skeleton of cyanogel serves as soft template to immobilize functional species. Cyanogel-derived nanomaterials exhibit superior activities and stabilities. The prepared materials exhibit promising applications for energy-related devices.